PENGUATAN BUDAYA LITERASI DI MEDIA SOSIAL DALAM PANDANGAN ISLAM - Gunawan, Gunawan; Sainun, Sainun; Gazali, Gazali (Ibn Khaldun University, Bogor, 2024)
In the era of science and technology, the use of social media can hardly be limited because it crosses space, time and place very quickly, so that the Islamic ummah is increasingly faced with various problems, both those that directly touch Islamic teachings and other problems that are still related to Islam and these problems require instruments of resolution. and one of those instruments is Islamic teachings/law. One of the problems that is currently widespread is the use of social media to spread hoaxes and hate speech which has an impact on national instability, social media such as FB, WA, Instagram, Twitter and so on which make it easier to meet in cyberspace. To ensure that there is no negative impact on the use of social media, a literacy culture is needed for all social media users, because by strengthening literacy culture, I, you and all of us will be able to filter and select every news spread by irresponsible people.